A Study on IoT-Enabled Smart Vehicles for Road Navigation and Ride Comfortability in Contemporary Vehicle Applications - Ekanem, Imoh Ime; Ikpe, Aniekan Essienubong; Ohwoekevwo, Jephtar Uviefovwe (Soft Computing Fusion with Applications, 2024)
Traditional navigation systems in vehicles often lack real-time data and personalized recommendations, leading to inefficient route planning and subpar ride comfortability. Drivers may encounter traffic congestion, road closures, and other obstacles that can disrupt their journey and increase stress levels. Additionally, the lack of connectivity and automation in vehicles can limit the ability to optimize routes, monitor vehicle performance, and enhance ride comfortability. With the advent of Internet of Things (IoT) technology, smart vehicles have the potential to address these issues by providing accurate and up-to-date information to drivers and passengers. The limitations highlight the conventional innovative solutions that can improve the overall driving experience and make transportation more convenient and enjoyable for users. The study adopted an argumentative approach combined with theoretical insights that involved a thorough analysis of existing literature and a case study on the trends, benefits, challenges, and potential impacts of IoT technology on the driving experience in modern vehicles. The research methodology included reviewing relevant studies on IoT technology, smart vehicles, transportation systems, and IoT-enabled vehicle features using online databases. The findings suggest that IoT-enabled smart vehicles have the potential to revolutionize road navigation and ride comfortability. By leveraging real-time data and connectivity features, these vehicles can provide drivers with accurate traffic updates, optimize routes based on current conditions, and even predict maintenance needs to prevent breakdowns. Regarding ride comfortability, IoT technology enables personalized settings for temperature, music, and seating preferences, as well as automated driving features that reduce driver fatigue and improve safety. The outcomes of this study highlight the transformative power of IoT-enabled smart vehicles in enhancing the driving experience and shaping the future of transportation. However, data privacy and security concerns must be addressed to fully realize IoT technology's benefits in smart vehicles.